KONDISI MAKRO EKONOMI DALAM PENGUATAN PAJAK DAERAH PADA STRUKTUR PENDAPATAN KOTA MAKASSAR - Haerial Haerial (AkMen JURNAL ILMIAH, 2016)
The purpose of this study is to analyze and quantify the effect of macro economic condition, hotel tax, and advertising tax on regional riel income. This study used secondary data obtained in the financial statements for 2009-2013 taken from regional income agent of Makassar municipality, inflation data from regional statistic body of Makassar. Technical studies using multiple linear Regression. The results in, showed that hotel tax, and advertising taxhas positive and significance influence on regional riel income, whereas macro economic condition has negative and the significance influence on regional riel income.